1993
DOI: 10.1007/bf01245341
|View full text |Cite
|
Sign up to set email alerts
|

Early postnatal hypoxia induces long-term changes in the dopaminergic system in rats

Abstract: A rat model of a mild, chronic, early postnatal hypoxia, characterized by long-term consequences in the behavioural outcome, was used to study long-term consequences in the dopaminergic system. Exposure of newborn rats to an early postnatal hypoxia (hypobaric hypoxia, 11 kPa pO2 in the inspiratory air, 2nd-10th day of life, 10 hours daily) brings about the following lasting neurochemical changes: an increased stimulated dopamine release rate from striatum slices by about 30%, an increased low affinity, high ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0
1

Year Published

1998
1998
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 20 publications
1
7
0
1
Order By: Relevance
“…Behavioral abnormalities in these rats are associated with enhanced activity of the nucleus accumbens-striatal dopaminergic system (Goto and O'Donnell 2002;Lipska and Weinberger 2000;Schroeder et al 1999) and with prefrontal dysfunction (Bertolino et al 2003;Lipska et al 2003;Tseng et al 2007), similar to the findings in schizophrenia patients (Weinberger et al 2001) An additional animal paradigm related to the neurodevelopmental hypothesis of schizophrenia modeling obstetric complications is neonatal exposure to hypoxia (Boksa and El-Khodor 2003;Verdoux and Sutter 2002). In this model, the animals exhibit a long-term increase in striatal dopamine release, increased locomotor activity in a novel environment, increased response to apomorphine, as well as impaired working memory, all of which have been implicated in schizophrenia (Decker and Rye 2002;Gross et al 1993;Hermans and Longo 1994;Lun et al 1990). Interestingly, it has been reported that more than 50% of schizophrenia candidate genes, e.g., AKT1, brain-derived neurotrophic factor (BDNF), CNR1, COMT, DNTBP1, NOTCH4, NRG1, NR4A2/NURR1 RELN, and RGS4, are subjected to regulation by hypoxia (Schmidt-Kastner et al 2006), further strengthening the neonatal hypoxia model as an animal model for schizophrenia.…”
Section: Introductionmentioning
confidence: 60%
“…Behavioral abnormalities in these rats are associated with enhanced activity of the nucleus accumbens-striatal dopaminergic system (Goto and O'Donnell 2002;Lipska and Weinberger 2000;Schroeder et al 1999) and with prefrontal dysfunction (Bertolino et al 2003;Lipska et al 2003;Tseng et al 2007), similar to the findings in schizophrenia patients (Weinberger et al 2001) An additional animal paradigm related to the neurodevelopmental hypothesis of schizophrenia modeling obstetric complications is neonatal exposure to hypoxia (Boksa and El-Khodor 2003;Verdoux and Sutter 2002). In this model, the animals exhibit a long-term increase in striatal dopamine release, increased locomotor activity in a novel environment, increased response to apomorphine, as well as impaired working memory, all of which have been implicated in schizophrenia (Decker and Rye 2002;Gross et al 1993;Hermans and Longo 1994;Lun et al 1990). Interestingly, it has been reported that more than 50% of schizophrenia candidate genes, e.g., AKT1, brain-derived neurotrophic factor (BDNF), CNR1, COMT, DNTBP1, NOTCH4, NRG1, NR4A2/NURR1 RELN, and RGS4, are subjected to regulation by hypoxia (Schmidt-Kastner et al 2006), further strengthening the neonatal hypoxia model as an animal model for schizophrenia.…”
Section: Introductionmentioning
confidence: 60%
“…They are directed partly towards the striatum, and partly towards the cortex, especially the medial frontal lobe, piriform and prepiriform cortex, entorhinal cortex and anterior cingulate cortex [1]. The sensitivity of dopaminergic neurons to hypoxia has been suggested in animal [6], and levodopa treatment helps to restore normal metabolic and cognitive functioning [13]. Interestingly therapeutic withdrawal at a late phase has no clear effect.…”
Section: Discussionmentioning
confidence: 99%
“…Exposure to oxygen restriction at an early neonatal age, rather than in utero, better models obstetric complications as a risk factor for schizophrenia since rodent brain maturation at about 1 week of age parallels the maturation stage of the prenatal human brain (Boksa 2004), even though neonates are self-breathing, which limits the resemblance to the prenatal state. Models of chronic mild neonatal hypoxia showed a long-term increase in striatal dopamine release (Decker et al 2003;Decker and Rye 2002;Gross et al 1993), reduction in neuronal myelination in the hippocampus and cerebellum (Olson and McKeon 2004;Weitzdoerfer et al 2004;Nyakas et al 1996), increased locomotor activity (Decker et al 2003;Hermans and Longo 1994), increased response to apomorphine (Lun et al 1990) and impaired working memory (Decker et al 2003), all implied in schizophrenia. Deficit in active avoidance response has also been reported, although not always replicated (Hoeger et al 2000;Lun et al 1993).…”
Section: Discussionmentioning
confidence: 98%